PENGARUH PEMBERIAN ANKLE STRATEGY EXERCISEDANCORE STABILITY EXERCISE TERHADAPKESEIMBANGAN DINAMIS LANSIA - Adenikheir, Annisa (Menara Ilmu, 2019)
Background: Dynamic balance is the maintenance of body equilibrium when the body is moving. Balance disorder is a common problem found among the elderly people. Problems that would arise from a balance disorder is an increased risk of falls among the elderly people. The purpose of : was to know the effect of ankle strategy exercise and core stability exercise on dynamic balance in elderly. Methods :is pre experimental using one group pre-test and post test. The population in this study is all elderly people in Posyandu lansia Pasar Baru Padang Panjang year 2018 which amounted to 72 elderly. Sampling in research using purposive sampling technique so that got sample as much 16 person elderly. The data collection used the Time up and Go test observation sheets measured before and after therapy. Result :the average time that was needed to do TUG test before intervention was 25,25 seconds and after intervention was 11,18 seconds. Based on wilcoxon test, p= 0,000 (p<0,05) it means that there are differentiation in dynamical balance for the elder before and after the exercise. Conclusion : Ankle Strategy Exercise and Core Stability Exercise can improve the dynamic balance of elderly this is evidenced by the decrease of time decrease time required in performing motion balance test using TUG test Key words : Elderly, ankle startegy exercise, core stability exercise, dynamic balance